Ярослав Ісаєвич. Україна давня і нова: народ, релігія, культура - Дзюба, О. М. (Український історичний журнал, 2025)
Ярослав Ісаєвич. Україна давня і нова: народ, релігія, культура. — Л., 1996. — 334 с.